A tributação do uso de dados de usuários como forma de promoção de justiça tributária na economia - Rodrigues, Cristina Barbosa (2024)
This thesis focus is the taxation for the use of Brazilian user data by technology the biggest companies in the digital economy (big techs) and investigates how new information and communication technologies impact on traditional tax concepts and models. Once they are processed, the information and data collected in the most diverse countries are an important asset for those companies to make more profit, wealth that is not properly taxed where it was generated, hence the need for a new and balanced redistribution of tax rights between jurisdictions. This qualitative research is based especially on the deductive method, starting from the study of broader subjects such as the digital economy and its main applications and transactions, going through its general taxation, to arrive at the international and national proposals of implementing a tax on big techs for using user data. For this purpose, it relies on documental (normative and jurisprudential) and bibliographical (doctrinal and journalistic) sources. Through this thesis, the purpose is to identify the developments and challenges, both for tax law and for international guidelines, caused by the changes arising from the digital economy, in order to promote not only a better understanding of the subject but also tax justice, particularly in developing countries such as Brazil, where much of this data is collected. In conclusion, as a way of guaranteeing tax justice, it is imperative to consider the economic exploitation of Brazilian users' data in the composition of the overall revenue of the main digital platforms. To this end, internationally, the States should increase international cooperation on the subject with the OECD and, domestically, Brazil and the other States where the population that contributes the most with data is concentrated should consider creating specific taxation for certain operations carried out in this context, as a way of battling the reduction of their tax base